2008
DOI: 10.1073/pnas.0711299105
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of interneuron programs and maintenance of selected spinal motor neuron fates by the transcription factor AML1/Runx1

Abstract: Individual spinal motor neuron identities are specified in large part by the intrinsic repertoire of transcription factors expressed by undifferentiated progenitors and maturing neurons. It is shown here that the transcription factor AML1/Runx1 (Runx1) is expressed in selected spinal motor neuron subtypes after the onset of differentiation and is both necessary and sufficient to suppress interneuron-specific developmental programs and promote maintenance of motor neuron characteristics. These findings show an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…1 I-K ). Using a previously characterized anti-Runx1 antibody (Stifani et al, 2008;Zagami and Stifani, 2010), we confirmed that ␤-gal expression overlapped with Runx1 immunoreactivity at all stages examined, demonstrating the presence of the Runx1 protein in ␤-gal ϩ cells ( Fig. 1 M, O).…”
Section: Runx1 Is Expressed In a Restricted Group Of Cells In The Devsupporting
confidence: 50%
See 1 more Smart Citation
“…1 I-K ). Using a previously characterized anti-Runx1 antibody (Stifani et al, 2008;Zagami and Stifani, 2010), we confirmed that ␤-gal expression overlapped with Runx1 immunoreactivity at all stages examined, demonstrating the presence of the Runx1 protein in ␤-gal ϩ cells ( Fig. 1 M, O).…”
Section: Runx1 Is Expressed In a Restricted Group Of Cells In The Devsupporting
confidence: 50%
“…LacZ/ϩ knock-in mice in which ␤-gal immunoreactivity faithfully reproduces Runx1 gene activation were examined to characterize Runx1 expression (North et al, 1999;Stifani et al, 2008;Zagami and Stifani, 2010). A small number of ␤-galexpressing cells was first detected in the forebrain of Runx1 LacZ/ϩ embryos at late embryonic stages ( Fig.…”
Section: Runx1 Is Expressed In a Restricted Group Of Cells In The Devmentioning
confidence: 99%
“…The blood-rescued Runx1-null pups were born apparently normal but were unable to feed and died within 1 d postpartum. Reactivation of the same Runx1 LacZ allele in the Tie2 + anatomic compartments led to similar postnatal mortality (21), which may result from abnormal skeletal or neural development (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Runx1 lacZ/+ mice were generated and genotyped as described in [11]. For embryonic staging, the day of appearance of the vaginal plug was considered as 0.5 embryological day (E0.5).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…E13.5 mouse embryos were collected and fixed in 2% paraformaldehyde, 10 mM sodium periodate, and 70 mM l-lysine for 2 hours; transferred to 30% sucrose for 24 hours. After freezing, 14µm cryostat sections were prepared and subjected to immunohistochemistry as described in [11] in order to identify specific MNs. All the resulting slices were captured with an EXi Retiga color camera (QImaging) mounted on an Axio Imager M1 microscope (Zeiss) with a 1.68x1.68µm in-plane resolution (Fig.…”
Section: Data Acquisitionmentioning
confidence: 99%